Risk Factors Affecting Mental Health During The Early Stages Of The Covid-19 Pandemic In High-Risk 50+ Population In The Czech Republic - Vaculíková, Jitka; Hanková, Magdalena (Journal of gerontological social work, 2022)
This study deals with key factors affecting mental health during the COVID-19 pandemic. The results are based on the longitudinal representative 50+ population-based multi-country panel study Survey of Health, Aging and Retirement in Europe (SHARE) in which representative samples of individuals in European countries plus Israel were collected. The goal is to turn the challenges of aging into opportunities as well as provide valid and reliable data for evidence-based policies. A total of 2,631 participants were interviewed by telephone in the Czech Republic during the initial stages of the COVID-19 outbreak in 2020. After a descriptive analysis showed that participants complied well with most preventative and protective COVID-19 measures, subsequent modeling using logistic regression analysis and a decision tree algorithm identified key determinants that have contributed to an understanding of variation in declared feelings of depression. We found that nervousness, previously unexperienced trouble with sleep, and self-rated health status before the COVID-19 outbreak and gender remained significant predictors of depression, from which statistically significant different categories concerning the percentage of depression could be formed. These identified potential risk factors should be considered in planning further supportive strategies for high-risk 50+ population.
Keywords: SARS-CoV-2; depression; share; Humans; risk factors; determinants; úzkost; rizikové faktory; Czech Republic; Česká republika; COVID-19; Anxiety; duševní zdraví; deprese; older adults; Mental Health; pandemie; Depression; lidé; Pandemics; Risk Factors